2020
DOI: 10.1016/j.envint.2020.106014
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of depression in relation to transportation noise exposure and noise annoyance in the SAPALDIA study

Abstract: Prospective evidence on the risk of depression in relation to transportation noise exposure and noise annoyance is limited and mixed. We aimed to investigate the associations of long-term exposure to source-specific transportation noise and noise annoyance with incidence of depression in the SAPALDIA (Swiss cohort study on air pollution and lung and heart diseases in adults) cohort.We investigated 4,581 SAPALDIA participants without depression in the year 2001/2002. Corresponding oneyear mean road, railway and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 111 publications
4
32
2
1
Order By: Relevance
“…Recently, the population-based SAPALDIA cohort in Switzerland found significant enrichment of DNA methylation relating to CRP, independent of other noise sources and air pollution, with road L den exposure. 36 This is in line with findings from novel experimental models, which found that traffic noise could induce oxidative stress and inflammation in the blood and the vasculature via an increased level of angiotensin II. 1 More evidence is needed to support this novel mechanism through systemic inflammation for the association between traffic noise and health outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…Recently, the population-based SAPALDIA cohort in Switzerland found significant enrichment of DNA methylation relating to CRP, independent of other noise sources and air pollution, with road L den exposure. 36 This is in line with findings from novel experimental models, which found that traffic noise could induce oxidative stress and inflammation in the blood and the vasculature via an increased level of angiotensin II. 1 More evidence is needed to support this novel mechanism through systemic inflammation for the association between traffic noise and health outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…Our own review found four high-quality prospective studies published since 2016 that reported risks ranging between 1.04 and 1.28 [32][33][34][35], although only half of these results achieved statistical significance [5,32,33]. A newer prospective study from Switzerland also found an increased risk of depression (RR = 1.06, 95% CI 0.93-1.22) that did not achieve statistical significance (possibly in part due to the low incidence of depression in the cohort: 11 cases per 1000 person-years) [36]. Nevertheless, we decided to include depression in our core analyses to determine depression attributable to road-traffic noise.…”
Section: Selection Of Outcomes (Clinical Endpoints)mentioning
confidence: 96%
“…In contrast, greater exposure to noise and air pollution has been associated with increased risk of depression (Braithwaite et al, 2019;Dzhambov & Lercher, 2019;Eze et al, 2020). The relationship between noise and poorer mental health may be mediated by noise annoyance, neighbourhood restorative quality, physical activity and sleep disturbance (Dzhambov et al, 2018;van den Bosch & Meyer-Lindenberg, 2019).…”
Section: Introductionmentioning
confidence: 99%